Love and Objective Reality in Spinoza's Account of the Mind's Power over the Affects. - Alanen, Lilli (Australasian Journal of Philosophy, 2023)
This paper explores Spinoza's therapy of passions and method of salvation through knowledge and love of God. His optimism about this method is perplexing: it is not even clear how his God, who is unlike any traditional notion of divinity, can be loved. Sorting out Spinoza's view involves distinguishing an ethics of bondage from another of freedom, and two corresponding notions of love of God. The paper argues that the highest kind of love—'pure intellectual love of God'—should not be understood as an affect at all, but instead as unimpeded intellectual activity. This suggestion requires reconsidering Spinoza's account of cognition, particularly his use of the Cartesian notions of objective and formal reality which are not only central to his theory of ideas but constitute the foundations of his salvation project.